A longitudinal mixed methods study describing the framing of eating disorders in Women’s Health articles from 2015 to 2017 - Webster, Kayley (The IIE, 2018)
There has been an estimated rise in the number of young women in South Africa developing eating disorders (Revelas, 2013). A study conducted by Angela Michel (2015) found that American beauty magazines were not including ‘effectual’ information about eating disorders. This study investigated how Women’s Health (Media24) articles about eating disorders from 2015 to 2017 framed eating disorders and whether ‘effectual’ information was included. Media Framing theory was used as the theoretical framework for this study. The researcher used mixed methods as the research approach and a coding schedule was created to code the articles based on identified frames and codes. The data was analysed using a descriptive statistical analysis and a thematic analysis. It was found that all seven articles included effectual information about eating disorders. Women’s Health (Media24) also had a unique way of representing the narrative frame in the ‘letters to the editor’ section and the articles included ‘effectual’ information such as ‘signs and symptoms’ and ‘expert medical advice’. This study contributed new insight into the field of Communication as it contributed to an understanding of how eating disorders were framed in South African beauty magazines and possibly could benefit sufferers of eating disorders who may read the articles for support.
Keywords: Media Framing Theory; efficacy; eating disorders; Women's Health; effectual information in magazine articles